Prosthetic transfer impression accuracy evaluation for osseointegrated implants - Assunção, Wirley Goncalves [UNESP]; Tabata, Lucas Fernando [UNESP]; Cardoso, Alessandra; Rocha, Eduardo Passos [UNESP]; Gomes, Erica Alves [UNESP] (Lippincott Williams & Wilkins, 2008)
Purpose: The objective of this study was to evaluate and compare 3 impression techniques for osseointegrated implant transfer procedures.Materials and Methods: (1) Group Splinted with Acrylic Resin (SAR), impression with square copings splinted with prefabricated autopolymerizing acrylic resin bar; (2) Group Splinted with Light-Curing Resin (SLR), impression, with square copings splinted with prefabricated light-curing composite resin bar; (3). Group Independent Air-abraded (IAA), impression with independent square coping aluminum oxide air-abraded. Impression procedures were performed with polyether material, and the data obtained was compared with a control group. These were characterized by metal matrix (MM) measurement values of the implants inclination positions at 90 and 05 degrees in relation to the matrix surface. Readings of analogs and implant inclinations were assessed randomly through graphic computation AutoCAD software. Experimental groups angular deviation with MM were submitted to analysis of variance and means were compared through Tukey's test (P < 0.05).Results: There was no statistical significant difference between SAR and SLR experimental groups and MM for vertical and angulated implants. Group IAA presented a statistically significant difference for angulated implants.Conclusion: It was concluded within the limitations of this study, that SAR and SLR produced more accurate casts than IAA technique, which presented inferior results.
Keywords: dental implants; prosthodontics; impression materials; impression techniques